ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Hayati, Zahratul; Masfufah, Masfufah; Atik, Nur Sri; Kaluku, Khartini; Wardani, Endah Kusuma (Ensiklopedia of Journal, 2024)
Anemia in pregnant women is a condition of mothers with hemoglobin (Hb) levels less than 11gr/dl which can cause the risk of bleeding, Fetal Growth Retardation (PJT), prematurity, Low Birth Weight (LBW), and stunting and even death in pregnant women. The purpose of the study was to analyze the factors associated with the incidence of anemia in pregnant women in the working area of UPTD Puskesmas Sidomulyo Outpatient. The purpose of the study was to analyze the factors associated with the incidence of anemia in pregnant women in the working area of UPTD Puskesmas Sidomulyo Outpatient Pekanbaru City. The research method used a cross sectional design with a population of pregnant women in trimester 2 and 3 with a total sample of 325 people. Sampling technique using systematic random sampling using secondary data taken from medical records. Data analysis was done univariate and bivariate. The results showed that there was a relationship between the age of pregnant women (p value: 0.00), parity (p value: 0.043) with the incidence of anemia in pregnant women. It is recommended to UPTD Puskesmas Sidomulyo Outpatient to increase the coverage of the implementation of the family planning program and increase the coverage of the implementation of the Blood Additive Tablet (TTD) program.Keywords: Anemia, Pregnant Women, Pregnancy, Parity